Two planetary systems with transiting Earth-sized and super-Earth planets orbiting late-type dwarf stars. (6th June 2018) - Díez Alonso, E; González Hernández, J I; Suárez Gómez, S L; Aguado, D S; González Gutiérrez, C; Suárez Mascareño, A; Cabrera-Lavers, A; González-Nuevo, J; Toledo–Padrón, B; Gracia, J; de Cos Juez, F J; Rebolo, R
ABSTRACT: We present two new planetary systems found around cool dwarf stars with data from the K2 mission. The first system was found in K2-239 (EPIC 248545986), characterized in this work as M3.0V and observed in the 14th campaign of K2. It consists of three Earth-sized transiting planets with radii of 1.1, 1.0, and 1.1 R⊕, showing a compact configuration with orbital periods of 5.24, 7.78, and 10.1 d, close to 2:3:4 resonances. The second was found in K2-240 (EPIC 249801827), characterized in this work as M0.5V and observed in the 15th campaign. It consists of two transiting super-Earths with radii 2.0 and 1.8 R⊕ and orbital periods of 6.03 and 20.5 d. The equilibrium temperatures of the atmospheres of these planets are estimated to be in the range of 380–600 K and the amplitudes of signals in transmission spectroscopy are estimated at ∼10 ppm.